Description of the immature stages and new host plant records of Deois (Deois) mourei (Berg) (Hemiptera: Cercopidae), a species newly recorded from Argentina and Paraguay - Foieri, Álvaro (2016)
Deois (Deois) mourei Cavichioli & Sakakibara (Hemiptera: Cercopidae) is recorded for the first time from Argentina and Paraguay. The eggs and immature stages of the species are described and illustrated; the main characters that distinguish instars are body size, color, number of flagellomeres, and number of tibial and metatarsomere spines. A key for identification of nymphs of D. (D.) mourei and a key to differentiate nymphs of the sympatric species D. (D.) mourei and Notozulia entreriana Berg are provided. In addition, a list of host plants of D. (D.) mourei in Argentina is given.